Maximizing pineapple (Ananas comosus) growth and yield: Effects of irrigation levels and NPK fertigation - PRADHAN, P.C.; DALAI, A.; SHARMA, R.P. (Journal of Soil and Water Conservation, 2026)
India must significantly increase its fruit crop production to meet the country’s growing food demands, particularly under the constraints of limited land, water, and changing climatic conditions. Pineapple, a nutritionally valuable crop, plays a critical role in this effort, with India ranking as the fifth-largest producer globally. The adoption of improved pineapple cultivation practices (PCP), including optimized irrigation levels and NPK fertigation, holds the potential to enhance water and fertilizer use efficiency compared to conventional cultivation practices (CCP). Field experiments were conducted over two consecutive years (2019-20 and 2020-21) at the Precision Farming Development Centre (PFDC) of Odisha University of Agriculture and Technology (OUAT), Bhubaneswar, to evaluate the effects of irrigation and fertigation levels on pineapple (Ananas comosus). The experiment followed a randomized block design with three replications across ten treatments. Three irrigation levels were tested: 100% (I1), 80% (I2), and 60% (I3) of crop evapotranspiration (ETc). Additionally, three fertigation levels were applied: 100% (F1), 80% (F2), and 60% (F3) of the recommended dose of fertilizer (RDF), based on soil test results (150 kg N, 60 kg P2O5, and 75 kg K2O per hectare). The study revealed that although 100% RDF fertigation with mulch (T4) resulted in the highest yield and superior fruit characteristics (length, girth, and weight), the treatment of 80% RDF fertigation with mulch (T5) performed comparably. This treatment achieved similar yields with reduced input use, contributing to lower production costs and increased profitability. Consequently, the 80% RDF fertigation with mulch emerges as a more resource-efficient approach, offering a sustainable option for pineapple cultivation.